Comunicação médico doente em oncologia. - Z M Santos; G Santos; P Abrantes (Acta Médica Portuguesa, 1994)
The authors analyse the problems of doctor/patient communication in Oncology with a particular incidence on the matter of diagnosis information. In a short theoretical review on the subject are debated the reasons that lead to an unbalanced power in doctor/patient relation, ships. It is pointed a general view of medical attitude along the last 25 years in several countries concerning diagnosis information and cultural differences, among other aspects. The AA seek to foresee reasons that may lead to a change on this matter. The medical class has been questioned about it's attitude on the diagnosis information of cancer. For that purpose a questionnaire was made and 80 doctors of HUC and CHC were interviewed. From the results the AA consider it is to be noted the following: 59% of the colleagues interviewed usually don't reveal the whole truth about the diagnosis; -Fear of patient's emotional reactions, is the most frequent reason to not to inform; There's the feeling among doctors that the knowledge of the truth has commonly a positive effect on doctor/patient relations.